Pengaruh Etos Kerja Islam Terhadap Kepuasan Kerja Karyawan Pada Waroeng Steak and Shake Surabaya - Saputro, Harjanto; Prasetyo, Ari (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research was aimed to investigate the effect of Islamic work ethics to the employee Satisfaction on Waroeng Steak & Shake in Surabaya. This study used questionnaires in primary data collection and quantitative approaches. Experiments were done using simple linear regression, where the dependent variable (Y) is the employee work satisfaction and the independent variable (X) is Islamic work ethics. The research sample were taken by census. The research sample was 33 employees working in Waroeng Steak & Shake Surabaya.Based on the findings, it obtained simple linear regression equation : Y = 0,929 + 0,684X. The magnitude of the influence of Islamic work ethics to the employees work satisfaction on Waroeng Steak & Shake in Surabaya is the R2 value of 0,423 (42,3%). The result show that employee work satisfaction on Waroeng Steak & Shake in Surabaya significantly affect by Islamic work ethics.